2020
DOI: 10.3390/su12093792
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Assessment of Green Infrastructure for Climate Change Adaptation in the Context of Urban Drainage Planning

Abstract: Green infrastructure (GI) contributes to improve urban drainage and also has other societal and environmental benefits that grey infrastructure usually does not have. Economic assessment for urban drainage planning and decision making often focuses on flood criteria. This study presents an economic assessment of GI based on a conventional cost-benefit analysis (CBA) that includes several benefits related to urban drainage (floods, combined sewer overflows and waste water treatment), environmental impacts (rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 31 publications
1
31
0
1
Order By: Relevance
“…In recent years, several researchers have assessed the impacts of climate change in different countries. At the same time, the resilience and adaptability of small rural societies to these new conditions have been studied [16][17][18][19][20][21]. Lal et al [22] found that the effects of climate change are generally more pronounced in rural areas than in urban areas of the United States.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, several researchers have assessed the impacts of climate change in different countries. At the same time, the resilience and adaptability of small rural societies to these new conditions have been studied [16][17][18][19][20][21]. Lal et al [22] found that the effects of climate change are generally more pronounced in rural areas than in urban areas of the United States.…”
Section: Methodsmentioning
confidence: 99%
“…Participants also received a short introduction paper, highlighting the concept of social justice to them as well. The questionnaire was developed based on three equity principles generally distinguished in the environmental-philosophical literature (Shue, 1999;Low and Gleeson, 1998;Paavola and Adger, 2002;Ikeme, 2003;Anand, 2004). (1) The egalitarian principle is based on Mill's and Bentham's utilitarian "greatest happiness principle".…”
Section: The Concept Of Social Justice In Bingomentioning
confidence: 99%
“…A group of studies have also used CBAs to measure the economic consequence of intervention projects focused on water programs [53,[65][66][67][68][69]. Work by Locatelli et al [70] assesses the economic impact of green infrastructure (GI) using a CBA that includes several benefits related to urban drainage in the Spanish cities of Barcelona and Badalona. Results reveal that the net present value of the GI is always positive, meaning GI has economic potential in the targeted urban regions.…”
Section: Literature Reviewmentioning
confidence: 99%